Analysis of Potential Drug–Drug Interactions in Pediatric HIV/AIDS Patients with Comorbidities at Dr. M. Djamil General Hospital Padang Based on Reliability and Risk Ratings - Elsa Marsellinda (Sciences and Clinical Pharmacy Research Journal, 2026)
To analyze potential drug-drug interactions among pediatric HIV/AIDS patients with comorbidities at RSUP Dr. M. Djamil Padang based on reliability and risk ratings. A descriptive retrospective study was conducted using medical records of pediatric HIV/AIDS patients treated in 2024. Potential DDIs were identified using the Lexicomp Drug Interactions Database. A total of 53 patients were included. Most patients were male (50.94%) and in the child age group (49.06%). A total of 107 potential drug-drug interactions were identified. Most interactions were classified as Good based on reliability rating (77.57%) and Category C (Monitor Therapy) based on risk rating (80.37%). No Category X interactions were found. Potential drug-drug interactions were common among pediatric HIV/AIDS patients with comorbidities, with most interactions requiring therapeutic monitoring.